THE EFFECT OF STATISTICS AND PROBABILITY LEARNING MODEL IMPROVEMENT ON STUDENT LEARNING OUTCOMES - Siti Fatimah Sihotang; Zuhri Zuhri (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2022)
The Statistics dan Probability class is one of the elective courses that have to be enrolled by students who have just joined the beginning of the semester. That is because studying Statistics and Probability is crucial in providing the first foundation for knowledge in other scientific domains. In actuality, though, a lot of students struggle with this course. Many students claim that they have trouble understanding the subjects they are learning, and they also have trouble figuring out how to answer the lecturer's questions. The low cognitive ability of students, which results in limited student creativity in problem-solving skills, is one of the elements contributing to students' failure to comprehend the subject. Of course, this is a severe issue if nothing is done right away. Based on these issues, researchers who were also lecturers improved the teaching strategies for all classes. This study aims to determine whether there is substantial interaction between class schedule and the development of learning model that impact exam scores by raising students' Statistics and Probability scores. The two-way Anova analysis principle is the basis of the study methodology. The enhancement of learning model used outside and inside the classroom was found to have a substantial interaction based on the research findings on fifty samples of students selected from different class. A significance score of 0.000 indicates that these findings are significant. In other words, a model is required to achieve better learning outcomes, which might make it simpler for students to commence learning and provide a common purpose for learning. Since multiple class schedules exist, each learning model necessitates a unique management system and learning environment.